Intraosseous focal venous malformation of the mandibular body: Cone beam computed tomography planning followed by piezoelectric knife resection and free bone graft reconstruction - Nikolić Živorad S.; Jelovac Drago B.; Šabani Melvil; Jeremić Jelena V.; Boričić Ivan (Vojnosanitetski Pregled)
Introduction. Intraosseous vascular malformation could be life-threatening due to uncontrolled hemorrhage after tooth extraction. According to biological behavior of this lesion, adequate diagnostic and treatment strategies are necessary in order to avoid possible complications. We reported cone beam computed tomography (CBCT) planning of an urgent en bloc resection of an intraosseous venous malformation by piezoelectric knife. Case report. A 55-year-old man was submitted to CBCT planning followed by piezoelectric knife resection of an intraosseous focal venous malformation of the mandibular body. Immediate reconstruction of the defect using iliac bone free graft was performed. The surgical treatment was uneventful and a 2-year follow-up revealed no signs of recurrence. Conclusion. Piezoelectric knife could provide precise, safe and bloodless procedure which is especially important in this pathology. Advantages of this technique are: lower risk of damaging soft tissue structures, precise osteotomy and bloodless surgery. Moreover, using piezosurgery bone knife, blood transfusion and blood transmitted diseases could be avoided. This case highlights the importance of CBCT as planning tool for resection of the mandible, using piezoelectric knife as safe method to achieve bloodless surgery. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 175075]